Development of mathematical model for the prediction of microwave signal attenuation due to duststorm - Elabdin, Zain; Islam, Md. Rafiqul; Khalifa, Othman Omran; Raouf, Hany Essam A.; Salami, Momoh Jimoh Emiyoka (2008)
Signal attenuation caused by duststorm is one of the major problems in utilization of microwave bands for terrestrial and space communication especially at desert and semi desert area. This paper presented a mathematical model developed to predict the microwave signal attenuation due to duststorm. The proposed model enables the convenient calculation of the microwave signal path attenuation which relates visibility, frequency, particle size and complex permittivity of duststorm. The predicted values from the mathematical model are compared with the measured values observed in Sudan and Saudi Arabia shows relatively close agreement.